The Correlation of Lipocalin-2 and Retinol Binding Protein-4 with the Inflammatory State in Iraqi Patients with T2DM - Wadood , Shatha Abdul; Al- Shawk , Refif Sabih; Sabir Shahla´a Fadil (Iraqi Journal of Science, 2022)
Adipokines are associated with insulin resistance and obesity-related metabolicdisorders in many diseases. The levels of Lipocalin-2 and Retinol binding protein-4were evaluated in sera of patients with Type 2 diabetes (T2DM) to study theassociation between them and the inflammatory state as established by high levels ofC - reactive protein and with atherogenicity. Serum Lipocalin-2 and Retinol bindingprotein-4 levels measured in 73 subjects: 48 patients with T2DM with the meanlevel of C- reactive protein 23.989 mg/dL. For comparison, 25 age- and gendermatchedcontrol participants enrolled with C- reactive protein CRP level 1.476mg/dL. The results showed that circulating Lipocalin-2, and Retinol binding protein-4 levels were significantly higher in T2DM patients when compared with that of thecontrol group (78.688vs.38.463ng/mL) and (0.0499vs.0.041μg/mL; P<0.05)respectively. Serum lipocalin-2 levels of patients group were negatively associatedwith RBP-4 (r= -0.248; P<0.039), and positively correlated with CRP (r=0.512;P<0.005) and with atherogenic index (AIP). Lipocalin-2, but not RBP-4, wasindependently associated with inflammatory state and atherogenicity that confirmthe presence of cardiovascular diseases risk. A study with a large number of patientsis needed to determine serum lipocalin-2 value as an early predictor for thedevelopment of cardiovascular diseases in type 2 diabetes patients.